Supervivencia del heminoptero braconido Opius concolor Szep. parasito de Dacus oleae Gmelin. en Olivares de Jaen - Jimenez, A.=700 1 Castillo, A.; Lorite, P.
(Es, En)
ilus., 8 ref.
Keywords: OPIUS CONCOLOR; DACUS OLEAE; INVERNACION; ESPAÑA